VISUALISASI RIWAYAT PERUNDANG – UNDANGAN DI NEGARA REPUBLIK INDONESIA (Information Technology and Telematics, 2015)
Abstract A country has to have regulations that serves to set our nation and state its citizens .In indonesia, socialization of the  regulation utilizes a web that was owned by almost all of a department of our government. The  legislation has history since the first issued until gets a change and his statutes. The history of regulations still difficult to be understod and to be read.The problem in this research is how to develop visualization of the legislation and the history. The purpose of this research is to build the visualization of the history of legislations in indonesia that the object of legislations taken from government website. This system uses prototype method of development and the system design uses DFD ( data flow diagram ) and flowchat. The software used are  xampp , php , json , a java script. To describe the visualization uses graph method. The Data of  the legislation that is put on by the user as input ( input ) will be processed and issued as output ( output ) that in the form of visualize the history of legislation and additional documentation such as  place the date and and who enacts a law. This research produce an visualize application the history of legislations in indonesia that can be used to know from the acts of legislation since the first time issued until until to be changed and statutes so that can be used easily. The keywords: xampp, a java the scripts, json, graph, visuals, legislation.